Human Development According to Buddhist Philosophy - Arkanit, Jiranit; Leeka, Jaras; Katasaro, Phramaha Paphon (Journal of Graduate MCU KhonKaen Campus, 2022)
The objective of the academic article was to present human development according to Buddhist philosophy. Humans can develop themselves to attain perfect human beings through the three principles (morality, concentration, and wisdom) fundamental processes for better human behavior training. The precepts will help develop the behaviors expressed in 3 bodily actions and 4 verbal actions. Concentration is the training of the mind to stay in the present while preventing the occurrence of 3 bad thoughts: wrong view, blame, vengeance, and wisdom will help to lead an efficient life. Until success and has a correct and good way of life until he attains true liberty, which is Nirvana